Nonspecific phospholipase C3 of radish has phospholipase D activity towards glycosylinositol phosphoceramide. Issue 23 (31st October 2022) - Hasi, Rumana Yesmin; Ishikawa, Toshiki; Sunagawa, Keigo; Takai, Yoshimichi; Ali, Hanif; Hayashi, Junji; Kawakami, Ryushi; Yuasa, Keizo; Aihara, Mutsumi; Kanemaru, Kaori; Imai, Hiroyuki; Tanaka, Tamotsu
Abstract : Glycosylinositol phosphoceramide (GIPC) is a major sphingolipid in the plasma membranes of plants. Previously, we found an enzyme activity that produces phytoceramide 1‐phosphate (PC1P) by hydrolysis of the D position of GIPC in cabbage and named this activity as GIPC‐phospholipase D (PLD). Here, we purified GIPC‐PLD by sequential chromatography from radish roots. Peptide mass fingerprinting analysis revealed that the potential candidate for GIPC‐PLD protein was nonspecific phospholipase C3 (NPC3), which has not been characterized as a PLD. The recombinant NPC3 protein obtained by heterologous expression system in Escherichia coli produced PC1P from GIPC and showed essentially the same enzymatic properties as those we characterized as GIPC‐PLD in cabbage, radish and Arabidopsis thaliana. From these results, we conclude that NPC3 is one of the enzymes that degrade GIPC. Abstract : Previously, we characterized glycosylinositol phosphoceramide (GIPC)‐specific phospholipase D (PLD) activity in Brassica plants. Here, after purification and peptide mass fingerprinting analysis of this protein, we found that the nonspecific phospholipase C3 (NPC3) exerts GIPC‐PLD activity in plants.